Impact of PCSK9 and acid ceramidase on obese hypothyroidism female patients (The Peerian Journal, 2024)
Proprotein Convertase subtilisin Kexin type 9 (PCSK9) is a serine protease composed of 692 residues. Acid ceramidase is an enzyme that hydrolyzed ceramide to sphingosine and fatty acids